Opuntia cochenillifera Cream Accelerates Incision and Burn Wound Healing in Streptozotocin-Induced Diabetic Mice by Enhancing Fibroblast - Indah Saraswati; Desy Armalina; Rivaldo Heru Setiawan; Najwan Muhammad Sinna; Sahila Nifa Arummaisya (The Prodia Education and Research Institute (PERI), 2025)
BACKGROUND: Diabetes mellitus (DM) often leads to chronic, slow-healing wounds due to impaired tissue regeneration and sustained inflammation, which can progress to diabetic ulcers. Opuntia cochenillifera has been reported to possess antioxidant and anti-inflammatory potential, making it a promising candidate for natural wound therapies. However, standardized topical formulations and in vivo evaluations are limited. This study was conducted to develop and assess the wound-healing effects of Opuntia cochenillifera cream in diabetic mice.METHODS: Forty-eight male Balb/C mice were randomly assigned to different groups: healthy control (HC), negative control (C−), positive control (C+), and treatment (T) groups. DM was induced by a single intraperitoneal injection of 180 mg/kgBW streptozotocin. After confirming hyperglycemia, incisions and burn wounds were created and monitored for 7 and 14 days. Wound healing was assessed macroscopically (incision length, width, and burn diameter) and microscopically (fibroblast proliferation and re-epithelialization). The formulated Opuntia cochenillifera cream was evaluated for pH, homogeneity, adhesion, and spreadability using standard topical formulation tests.RESULTS: The formulated cream exhibited good homogeneity, adhesion (4.97 s), spreadability (5.10 cm), and skin-compatible pH (6.44). Phytochemical analysis confirmed the presence of flavonoids, tannins, terpenoids and alkaloids. In vivo, Opuntia cochenillifera cream significantly accelerated wound closure and increased fibroblast proliferation compared to the C− group (p<0.05). Its effects were comparable to those of the standard treatment for burn wounds and superior for incision wounds, demonstrating enhanced fibroblast activity and more organized re-epithelialization.CONCLUSION: Opuntia cochenillifera cream effectively improves wound healing in diabetic mice through the enchantment fibroblast activity and organized re-epithelialization. These findings support the potential of this formulation as a natural topical therapy for diabetic wounds, warranting further mechanistic investigation.KEYWORDS: Opuntia cochenillifera, diabetic wound, wound healing, topical cream, phytochemical